2021
DOI: 10.1038/s41419-021-04388-y
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus spp. create a protective micro-ecological environment through regulating the core fucosylation of vaginal epithelial cells against cervical cancer

Abstract: Vaginal dysbiosis often occurs in patients with cervical cancer. The fucosylation of mucosal epithelial cells is closely related to microbial colonization, and play an important role in protecting the vaginal mucosal epithelial cells. However, no reports on the relationship between vaginal dysbiosis and abnormal mucosal epithelial cell fucosylation, and their roles in the occurrence and development of cervical cancer are unavailable. Here we report that core fucosylation levels were significantly lower in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…Furthermore, L. iners , a strain that is the most common vaginal bacterium in healthy women ( 56 ), was found to be lower in HPV infection, HPV persistence, and Ca, but higher in HSIL. For example, decreased L. iners numbers have been linked to HPV infection, HPV persistence, and Ca ( 19 , 27 , 28 ). Alternatively, the presence of pre-cancer and cancer in women is associated with a high relative abundance of L. iners ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, L. iners , a strain that is the most common vaginal bacterium in healthy women ( 56 ), was found to be lower in HPV infection, HPV persistence, and Ca, but higher in HSIL. For example, decreased L. iners numbers have been linked to HPV infection, HPV persistence, and Ca ( 19 , 27 , 28 ). Alternatively, the presence of pre-cancer and cancer in women is associated with a high relative abundance of L. iners ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…This intraspecific diversity may be a crucial determinant of structural stability by buffering the dominant Lactobacillus configuration against disturbances ( 58 ). A recent study indicated that the L. iners metabolite, lactate, could inhibit the proliferation and migration of cervical cancer cells ( 19 ). With respect to co-occurrence patterns, suppressed Lactobacillus species L. iners was positively associated with Gardnerella ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the complicated microenvironment of cancer cells, however, these metabolites can also inhibit or accelerate the proliferation of malignant tumors (Zadravec, Štrukelj and Berlec, 2015; Homburg et al ., 2017). In fact, one previous study showed that ATCC L. iners (used as our non-cancer control) actually inhibited the proliferation and migration of cervical cancer cells by activating the WNT pathway in epidermal cells (Fan et al ., 2021). In HPV-related cervical cancer, the presence of Lactobacillus spp has been shown to widely vary with a typically reduced prevalence of L. crispatus and an L .…”
Section: Discussionmentioning
confidence: 99%
“…As a carcinogenic factor, HPV infection can also cause cancers in the vulva, anus, and oropharynx [ 3 ]. The carcinogenic mechanism of HPV infection is shown to be related to vaginal microecology, inflammatory factors, genetics, and immune function [ 4 , 5 ]. This study analyses the clinical effect of drug therapy on HPV infection, aiming to provide novel references for the improvement of vaginal microecology and alleviation of inflammatory factors in HPV-infected patients.…”
Section: Introductionmentioning
confidence: 99%